Da-Cheng-Qi decoction improves severe acute pancreatitis-associated acute lung injury by interfering with intestinal lymphatic pathway and reducing HMGB1-induced inflammatory response in rats - Xiaowen Liu; Lin Yuan; Yishuang Tang; Yue Wu; Jing Kong; Bingduo Zhou; Xiaosu Wang; Min Lin; Yading Li; Gaofan Xu; Yi Wang; Tingting Xu; et al. (Pharmaceutical Biology, 2023)
AbstractContext Da-Cheng-Qi Decoction (DCQD) has a significant effect on Severe Acute Pancreatitis-Associated Acute Lung Injury (SAP-ALI).Objective To explore the mechanism of DCQD in the treatment of SAP-ALI based on intestinal barrier function and intestinal lymphatic pathway.Materials and methods Forty-five Sprague-Dawley rats were divided into three groups: sham operation, model, and DCQD. The SAP model was induced by a retrograde infusion of 5.0% sodium taurocholate solution (1 mg/kg) at a constant rate of 12 mL/h using an infusion pump into the bile-pancreatic duct. Sham operation and model group were given 0.9% normal saline, while DCQD group was given DCQD (5.99 g/kg/d) by gavage 1 h before operation and 1, 11 and 23 h after operation. The levels of HMGB1, RAGE, TNF-α, IL-6, ICAM-1, d-LA, DAO in blood and MPO in lung were detected using ELISA. The expression of HMGB1, RAGE, NF-κB p65 in mesenteric lymph nodes and lung were determined.Results Compared with SAP group, DCQD significantly reduced the histopathological scoring of pancreatic tissue (SAP, 2.80 ± 0.42; DCQD, 2.58 ± 0.52), intestine (SAP, 3.30 ± 0.68; DCQD, 2.50 ± 0.80) and lung (SAP, 3.30 ± 0.68; DCQD, 2.42 ± 0.52). DCQD reduced serum HMGB1 level (SAP, 134.09 ± 19.79; DCQD, 88.05 ± 9.19), RAGE level (SAP, 5.05 ± 1.44; DCQD, 2.13 ± 0.54). WB and RT-PCR showed HMGB1-RAGE pathway was inhibited by DCQD (p < 0.01).Discussion and conclusions DCQD improves SAP-ALI in rats by interfering with intestinal lymphatic pathway and reducing HMGB1-induced inflammatory response.